Consuming Life after Anti-Trafficking - Henriksen, Sofie (Anti-Trafficking Review, 2018)
The rise of transnational, market-based anti-trafficking organisations has expanded the anti-trafficking domain to include Western corporations and consumers. In an effort to improve living conditions for survivors of trafficking, these organisations sell commodities produced by former victims or women at risk of human trafficking and brand them as symbols of a new and better life after anti-trafficking. Thus, life after anti-trafficking is not isolated to the locations of the trafficking victims, but occurs in distant areas and among diverse groups of people. This article investigates how representations of life after anti-trafficking engage consumers, corporations and NGO workers in New York City through the sale and purchase of ‘slave-free’ products made by Southeast Asian women deemed ‘survivors of trafficking’. The ethnographic data illustrates how life after anti-trafficking unfolds in the context of US corporate and consumer culture and intersects with capitalist discourses of freedom, consumer ethics and politics of market-based aid. Consequently, life after anti-trafficking creates new consumer identities, anti-trafficking aid strategies and business opportunities detached from the actual victims of human trafficking.